Changing the past: retroactive choice of law and the protection of third parties in the European regulations on patrimonial consequences of marriages and registered partnerships - Rademacher, Lukas (CUADERNOS DE DERECHO TRANSNACIONAL, 2018)
Two forthcoming EU Regulations are going to address, inter alia, the law applicable to the patrimonial consequences of marriages and registered partnerships. Under the Regulations, spouses and partners will not only be able to choose the applicable law but they are also granted the right to give their choice of law retroactive effect. Although the patrimonial consequences of marriages and partnerships are of relevance primarily to the spouses and registered partners, they may also directly affect the legal position of third parties. The aim of this paper is to identify and analyze the risks for third parties inherent in a retroactive change of the applicable law and the measures implemented in the Regulations to safeguard third party interests.